First record of Hysterothylacium fabri (Rudolphi 1819) Deardorff and Overstreet 1980 from Scomber Colias of the South Atlantic waters - Agostinho, Beatriz Narciso [UNESP]; Fragoso, Lúcia do Valle [UNESP]; Serrano, Thaíssa Duarte [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Vera, Manuel; Porto-Foresti, Fábio [UNESP]; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (Springer Nature, 2020)
Among several marine pelagic species of the Brazilian coast, Scomber colias Gmelin, 1789 (Perciformes: Scombridae) stands out for having great economic importance, since it is widely used as a food resource and presents moderate vulnerability. Twenty specimens of S. colias were purchased from October 2015 to October 2016 from the coast of Santa Catarina, Brazil. In the present study, we recorded Hysterothylacium fabri (Rudolphi, 1819) (Deardorff and Overstreet, Proc Biol Soc Wash 93(4):1035–1079 1980) from the S. colias intestine using an integrative taxonomy approach, where morphological data are used in combination with partial sequences of the ITS gene, to validate the taxonomic status of the species and establish their relationships with other members of the genus. This species is being recorded for the first time in the South Atlantic and S. colias. The specimens of H. fabri collected in this study parasitizing S. colias presented morphology similar to the other specimens already registered parasitizing other hosts. The distance matrix generated showed that the partial sequences obtained in this study were more similar to sequences of Hysterothylacium sp. collected in China. In phylogenetic analysis, the two detected haplotypes of this study were grouped with H. fabri haplotypes deposited in GenBank in a monophyletic subclade.
Keywords: Hysterothylacium; Morphology; Phylogenetic analyses; Scomber colias; SEM